Disease burden and high-risk populations for complications in patients with acute respiratory infections: a scoping review - Cui, Chendi; Timbrook, Tristan T.; Polacek, Cate; Heins, Zoe; Rosenthal, Ning A. (Frontiers in Medicine, 2024)
Background Acute respiratory infections (ARIs) represent a significant public health concern in the U.S. This study aimed to describe the disease burden of ARIs and identify U.S. populations at high risk of developing complications. Methods This scoping review searched PubMed and EBSCO databases to analyze U.S. studies from 2013 to 2022, focusing on disease burden, complications, and high-risk populations associated with ARIs. Results The study included 60 studies and showed that ARI is associated with a significant disease burden and healthcare resource utilization (HRU). In 2019, respiratory infection and tuberculosis caused 339,703 cases per 100,000 people, with most cases being upper respiratory infections and most deaths being lower respiratory infections. ARI is responsible for millions of outpatient visits, especially for influenza and pneumococcal pneumonia, and indirect costs of billions of dollars. ARI is caused by multiple pathogens and poses a significant burden on hospitalizations and outpatient visits. Risk factors for HRU associated with ARI include age, chronic conditions, and socioeconomic factors. Conclusion The review underscores the substantial disease burden of ARIs and the influence of age, chronic conditions, and socioeconomic status on developing complications. It highlights the necessity for targeted strategies for high-risk populations and effective pathogen detection to prevent severe complications and reduce HRU.